2015
DOI: 10.1785/0120140134
|View full text |Cite
|
Sign up to set email alerts
|

A Ground‐Motion Predictive Model for Iran and Turkey for Horizontal PGA, PGV, and 5% Damped Response Spectrum: Investigation of Possible Regional Effects

Abstract: We present a ground-motion prediction equation (GMPE) for Turkey and Iran to investigate the possible regional effects on ground-motion amplitudes in shallow active crustal earthquakes. The proposed GMPE is developed from a subset of the recently compiled strong-motion database of the Earthquake Model of the Middle East Region project (see Data and Resources). A total of 670 Turkish and 528 Iranian accelerograms with depths down to 35 km are used to estimate peak ground acceleration, peak ground velocity, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
36
1
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 132 publications
(46 citation statements)
references
References 55 publications
(42 reference statements)
4
36
1
5
Order By: Relevance
“…As magnitude dependency for τ SS values was not observed in this study, they are suggested in table 2 as constants although between-event standard deviations, τ, of [1] have magnitude dependency. In figure 9, variation of betweenevent standard deviation and source corrected between-event standard deviation values with spectral period is given for M w <6.0 and M w >6.5 events.…”
Section: Source Corrected Between-event Standard Deviation (τ Ss )contrasting
confidence: 53%
See 4 more Smart Citations
“…As magnitude dependency for τ SS values was not observed in this study, they are suggested in table 2 as constants although between-event standard deviations, τ, of [1] have magnitude dependency. In figure 9, variation of betweenevent standard deviation and source corrected between-event standard deviation values with spectral period is given for M w <6.0 and M w >6.5 events.…”
Section: Source Corrected Between-event Standard Deviation (τ Ss )contrasting
confidence: 53%
“…As a result magnitude independent event corrected single station standard deviations and source corrected between-event standard deviations are suggested (table 2). In order to preserve the [1] suggested within-event standard deviation-spectral period model for the event corrected single station standard deviations, the maximum likelihood approach was adopted. In figure 5, variation of within-event standard deviation and event corrected single station standard deviation values with spectral period is given for M w <6.0 and M w >6.5 events.…”
Section: Event Corrected Single Station Standard Deviation (φ Ss )mentioning
confidence: 99%
See 3 more Smart Citations